Malayic Aborigines of Malaysia: A Study in Subgrouping - Omar, Asmah Haji; Yahaya, Samsur Rijal (Advances in Social Sciences Research Journal, 2018)
Malaysian aborigines can only be located in Peninsular Malaysia or Malaya. Linguistically, they are divided into two main groups, based on the languages they speak: one consisting of speakers of languages belonging to the Austronesian stock which places them together with the Malays, and the other of speakers of the Austroasiatic stock which relates them to the Mon-Khmer family of the hill tribes of Burma, Thailand, Cambodia and Vietnam. This article focuses of the first group, consisting of six speech systems, examining their subgrouping based on their geo-history of settlement as well as the linguistic relationship between members of the subgroups. The result of this subgrouping is that five of the six are in dialectal relationship with Malay, while the sixth (originating from Sumatra) is a language in its own right. All the six can be linked to an ancestor form, the Proto-Malayic.